2017
DOI: 10.1021/acs.jpcc.7b07283
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light-Emitting Si Quantum Dots with Mesoporous and Amorphous Features: Origin of Photoluminescence and Potential Applications

Abstract: Recently, Si quantum dots (QDs) with porous and amorphous characteristics have shown tremendous potential applications in photovoltaics and biomedical fields. However, in general, their preparation involves meticulous synthetic procedures. Herein, we present the first report of the synthesis of Si QDs in aqueous solution with amorphous and porous features using γ-ray irradiation, which is a facile, one-pot, and reproducible approach. Fourier transform infrared and X-ray photoelectron spectroscopy indicated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 102 publications
0
14
0
Order By: Relevance
“…A control experiment was conducted wherein Se NPs were synthesized in aqueous solution in the absence of RTILs. The reaction mixture comprised a N 2 -bubbled aqueous solution of SeO 2 and tert -butanol (1 M; to quench • OH). ,,, The experimental parameters (such as absorbed dose and precursor concentration) were kept the same as in the case of experiments in the presence of RTILs. On irradiation of the reaction mixture, Se NPs were formed, as was indicated from the appearance of the red-orange color.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A control experiment was conducted wherein Se NPs were synthesized in aqueous solution in the absence of RTILs. The reaction mixture comprised a N 2 -bubbled aqueous solution of SeO 2 and tert -butanol (1 M; to quench • OH). ,,, The experimental parameters (such as absorbed dose and precursor concentration) were kept the same as in the case of experiments in the presence of RTILs. On irradiation of the reaction mixture, Se NPs were formed, as was indicated from the appearance of the red-orange color.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this perspective, a methodology of clubbing the radiation-mediated technique with the host matrix of solvents such as room-temperature ionic liquids (RTILs) could be a promising approach. Electron beam-induced nanomaterial synthesis is a versatile technique with several inherent advantages, such as facileness, nanocharacteristic-maneuvering parameters (such as absorbed dose and dose rate), time efficiency, scale-up potential, and not requiring any external reducing agents. In the current work, an electron beam was used to generate reducing species, deriving nucleation that eventually leads to the formation of α-Se NPs, while RTILs played multiple roles: as a host matrix, a source of reducing species, and a stabilizer. Nonetheless, apart from the synthesis of α-Se NPs with prolonged stabilization, the main objective of the current work was to investigate the effect of the nature of cation–anion combinations (in RTILs) on the size and phase stability of α-Se NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, lattice strain typically exists in nanoscale materials, which could influence the band structure of indirect band gap materials. In addition, dissolution–recrystallization processes caused by water might initiate the formation of emissive centers which could be possibly generated by defects or surface states in PRMs. ,, It is well-known that surface defects can be easily generated by oxygen- or moisture-induced reorientation of crystal structure or decomposition. Indeed, we also observed that PL inactive CsPb 2 Br 5 single crystals emit green photoluminescent after prolonged exposure to a humid atmosphere (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…In the Si 2p XPS spectrum (Figure 3C), the broad peak was fitted by three components at 102.15, 102.55, and 103.22 eV, corresponding to Si atoms involved in Si−C, Si−O−H, and Si−O−Si species, respectively, which were consistent with the formation of silica networks via hydrolysis and condensation of APTMS during the reaction. 38,39 In the N 1s spectrum (Figure 3D), the broad peak was fitted by two components at 399.36 and 400.26 eV, assigned to the N atoms in N−C and N−H bonds, respectively. 17,40 It was deduced that there were plenty of amino and silanol groups on the surface of the OSi NPs, which are responsible for their excellent dispersity in the aqueous phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…TEM observation revealed that the product was nanoparticles nearly spherical in shape, with an average size of 3.4 ± 0.4 nm (Figure A), corresponding to a hydrodynamic diameter of 5.8 nm (Figure S4). XRD pattern of the powdered nanoparticles showed a broad peak centered at 2θ = 21.5° (Figure S5), revealing the amorphous character of the nanoparticles. , MALDI-TOF mass spectrometry was employed to identify the composition of the nanoparticles (Figure B). The peak at the mass to charge ratio ( m / z ) of 2618.9 was assigned to the composition of [(ICG′) 2 (hAPTMS) 9 + Na] + , in which hAPTMS represents the hydrolytic APTMS molecules that may cross-link each other to construct the silica network, and ICG′ represents the product from the ICG molecule after the addition reaction.…”
Section: Resultsmentioning
confidence: 99%